Enhancing Creative Writing Skills in Foreign Language Learners Through Innovative Learning Strategies - Akbar Alfathan; Indah Kurniasari (Institute of Accounting Research and Novation (IARN), 2024)
This research investigates the effectiveness of innovative learning strategies in enhancing creative writing skills among foreign language learners. The study employs a mixed-methods approach, combining both quantitative (pre-test and post-test) and qualitative (surveys and interviews) data collection techniques. The experimental group, exposed to digital storytelling, collaborative writing, gamification, and visual prompts, demonstrated significant improvements in vocabulary richness, grammatical accuracy, coherence, and creativity, compared to the control group, which followed traditional writing instruction. The findings reveal that innovative methods not only foster better technical writing skills but also increase student motivation, engagement, and emotional connection to the language. These results align with and extend previous research on the role of technology and collaborative learning in language acquisition, highlighting the importance of creativity in language learning. This study suggests that integrating innovative, student-centered methods into foreign language instruction can provide a more dynamic, effective, and engaging learning environment. The implications for teachers, curriculum designers, and language learners are discussed, advocating for a more creative and interactive approach to language education.